CHARACTERIZING THE INTERNET AS AN ESSENTIAL ORGANIZATIONAL RESOURCE: RESULTS FROM A STUDY AT THE NATIVE MEN’S RESIDENCE (Canadian Journal of Native Studies, 2026)
This paper presents the results of research into the role of the internetin supporting the day-to-day activities, rehabilitation efforts, and essentialservice needs of clients and residents at the Native Men’s Residence(Na-Me-Res), a homeless services and outreach shelter operating in Toronto,Canada. The motivating interest of the study is to ascertain theextent to which the internet constitutes an essential technology resourcethat facilitates the delivery of Na-Me-Res’s core services, as well as inthe rehabilitation and employment activities of its residents. The resultshighlight the way precarious and unstable internet access can compromisethe abilities of Na-Me-Res clients to secure employment and longtermhousing, as well as their overall well-being.